Phoenician identities in Roman times: an issue of negotiated “glocal” identities from the East to the West - Machuca Prieto, Francisco (My University, 2022)
Now a days we know that the Phoenician communities of the East and the West do not disappear after the Roman conquest. For example, the Phoenicians of what is today the southern coasts of Spain continued to shape their own cultural and political destiny despite the powerful impact of the Roman. In the Syria-Phoenicia region, the Phoenician identity, as a symbolic identity, survived for long in the empire. Some authors from there, in different genres, and men pursuing elite careers found Phoenician claims useful and constructive for their own interests. Roman imperialism in Hispania clearly resulted in struggles over territory, sovereignty and cultural identity, but the archaeological and literary evidences points to a reality different than that underlying much of modern narratives of opposition. Usually, those struggles have been conceptualized as Roman versus local identities, but not as a generational choices involving old and new practices. In the case of Phoenician communities of the Roman Empire, the survival of cultural elements rooted in traditions prior to the arrival of Rome certainly does not indicate an active and hostile resistance to Roman customs. On the contrary, this continuity is seen as a renovation, a way of giving free rein to integration without renouncing the particularities. This phenomenon could be linked to the need for legitimation of the local elites, immersed in the complex game of identity oppositions and aggregations that held the ideological structures of Rome and its imperium, given the considerable degree of flexibility shown concerning the integration of the conquered peoples.
Keywords: Identidad étnica; Fenicios; Roma -- Historia -- 0284-0476 (Bajo Imperio); Globalización; Civilización romana; Etnicidad; Imperio romano